SENI KERAJINAN LAKUER SEBAGAI IDENTITAS BUDAYA LOKAL PALEMBANG DAN SARANA INDUSTRI KREATIF DALAM ERA GLOBALISASI - Husni Mubarat (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
The era of globalization or also known as the free market is an age where competition is increasingly open economy dominated by global capitalism. In the face of such a situation and condition of each country must be prepared to capitalize on the potential possessed by each country. Indonesia as a nation that has a wealth of natural and cultural course can be used as a potential in the era of globalization. One of the efforts that must be done is to prepare human resources creative and productive, so that Indonesian people capable of creating jobs both for himself and for others. One of the cultural products that can be used is the art of craft, such as craft Lakuer Palembang. Palembang Lakuer craft products have the potential to be developed as a creative industry. This craft is not only value-nlai beauty, but also can be used as a means of supporting the interior of homes, hotels and offices, such as cabinets, tables, slap betel, Lehar, and ornamental urns. In addition to having economic value that is the creative industry, this craft can also function as a media community to recognize local cultural identity. Therefore, the government's role in developing this craft has an important role, so as to improve the community economy Palembang and as a preservation of local cultural products of Palembang.Keywords: Palembang Lakuer Craft, Creative Industries, and the era of globalization